Forecasting future demand and planning the generations of electricity in Sabah - 250832 Alexander Jumin; Alias Warjan, supervisor; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2007